Banana starch nanocomposite with cellulose nanofibers isolated from banana peel by enzymatic treatment: In vitro cytotoxicity assessment - Tibolla, H.; Pelissari, F. M.; Martins, J. T.; Lanzoni, E. M. [UNESP]; Vicente, A. A.; Menegalli, F. C.; Cunha, R. L. (Elsevier, 2019)
The potential use of cellulose nanofibers (CNFs) as a reinforcing agent in banana starch-based nanocomposite films was investigated. CNFs were isolated from banana peel (Musa paradisiaca) by enzymatic hydrolysis. Banana starch-based nanocomposite films were prepared with CNFs using the casting method. CNFs effect on cell viability and on nanocomposite films properties’ was investigated. The cytotoxicity of CNFs was assessed on Caco-2 cell line. CNFs were not cytotoxic at 50–2000 μg/mL. However, CNFs above 2000 μg/mL significantly decreased cell viability. Topography analysis showed that the incorporation of CNFs modified the film structure. The nanocomposites exhibited a complex structure due to strong interactions between CNFs and starch matrix, promoting a remarkable improvement on mechanical and water barrier properties, opacity and UV light barrier compared to the control film. CNFs can offer a great potential as reinforcing material for starch-based nanocomposite films, producing a value-added food packaging from a waste material.
Keywords: Cellulose nanofibers; Enzymatic hydrolysis; Nanofiber cytotoxicity; Starch composite